2019
DOI: 10.1016/j.clbc.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Potential Novel Therapy Targets in Neuroendocrine Carcinomas of the Breast

Abstract: Neuroendocrine breast cancer lacks specific therapy, but similar common neuroendocrine carcinomas may offer guidance for therapy development. This study, for the first time, identified several biomarkers for targeted therapy approaches in patients with breast neuroendocrine carcinoma. Introduction: Neuroendocrine carcinoma (NEC) of the breast is a rare, special type of breast cancer, reportedly constituting 2% to 5% of all breast cancers. Although breast NEC does not have a specific targeted therapy, several n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Nevertheless, targeting PIK3CA in metastatic NECB could represent an intriguing therapeutic strategy, given the recent results achieved with the use of alpelisib in a population affected from HR positive, HER2 negative advanced breast cancer [ 73 ]. In their recent series, Vranic et al found a TROP-2 protein expression in 21%, suggesting that a small proportion of NEBCs may be sensitive to target therapy with sacituzumab govitecan [ 74 , 75 ]. To date, all currently approved biomarkers of response to immune checkpoint inhibitors (PD-L1 expression, high tumor mutational burden and microsatellite instability status) have proven negative, suggesting that patients with NEBC are not ideal candidates for immunotherapy [ 69 , 74 ] (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, targeting PIK3CA in metastatic NECB could represent an intriguing therapeutic strategy, given the recent results achieved with the use of alpelisib in a population affected from HR positive, HER2 negative advanced breast cancer [ 73 ]. In their recent series, Vranic et al found a TROP-2 protein expression in 21%, suggesting that a small proportion of NEBCs may be sensitive to target therapy with sacituzumab govitecan [ 74 , 75 ]. To date, all currently approved biomarkers of response to immune checkpoint inhibitors (PD-L1 expression, high tumor mutational burden and microsatellite instability status) have proven negative, suggesting that patients with NEBC are not ideal candidates for immunotherapy [ 69 , 74 ] (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…(MLH1, MSH2, MSH6, and PMS2) (clones and thresholds for positivity are provided in Table S1). 4,6,7 Both ER and PR were positive in the majority of cases (8+/9 cases each) ( Table 1). AR was positive in 7/9 cases (78%) without the presence of the ARv7 splice variant.…”
mentioning
confidence: 91%
“…In spite of substantial progresses in breast cancer treatment, detection of novel therapeutic targets for overcoming current obstacles is still required. In recent years, inhibition of cellular and molecular mechanisms that interfere with development of breast cancer is one of the critical diagnostic and therapeutic strategies (1)(2)(3). Nicotinamide phosphoribosyltransferase (NAMPT) is known as the rate-limiting enzyme in the salvage biosyn thetic pathway of nicotinamide adenine dinucleotide (NAD) (4,5) and is considered a critical enzyme that plays important roles in an extensive range of biological activities such as metabolism and immune response.…”
Section: Introductionmentioning
confidence: 99%